The Effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Indosat Tbk in 2013-2023 (Case Study on a Company Listed on Indonesia Stock Exchange) - Reynaldy Pratama Saputra; Tri Endar Susianto (Formosa Journal of Social Sciences (FJSS), 2024)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Debt To Equity Ratio (DER) on Return On Assets (ROA) at PT. Indosat Tbk from 2013 to 2023. This research method is quantitative using secondary data from PT Indosat's financial statements. The sampling technique was carried out by purposive sampling with specific criteria, namely the quarterly financial statements of PT. Indosat Tbk during the period 2013-2023. The Classical Assumption Test was used to test the research instrument, as well as Pearson Product Moment correlation analysis, coefficient of determination, t-test, f-test, and multiple linear regression to measure the influence of variables. The findings show that the relationship between TATO and ROA is very low with a correlation value of 0.146, while the relationship between DER and ROA is also very low with a correlation value of 0.115. Based on the determination analysis, the contribution of TATO and DER to ROA is only 3.2%, with 96.8% influenced by other factors outside the scope of this study